Landslide Risk Analysis in Kelud Volcano, East Java, Indonesia - Syamsul Bachri; Sumarmi Sumarmi; Sugeng Utaya; Listyo Yudha Irawan; Lela Wahyu Ning Tyas; Farizki Dwitri Nurdiansyah; Alif Erfika Nurjanah; Rahmat Wirawan; Akhmad Amri adillah; Denny Setia Purnama (Faculty of Geography, Universitas Gadjah Mada, 2021)
Pandansari village became one of the villages that has frequent landslide events in the period 2009-2015 compared with the surrounding area in Malang regency. The purpose of this study was to determine the level of landslide risk located within an active volcano. To enhance the comprehensive analysis of landslide disasters, we used a risk concept in this study. The landslide risk analysis was based on 3 determinants, namely hazards, community vulnerability, and regional capacity. The data collections were conducted using observation and documentation for landslide hazards and interviews as well as Focus Group Discussion (FGD) for vulnerability and capacity aspects. The interviewed were applied for community and local government of Pandansari village. The recorded interviews were transcribed and analyzed according to recurrent themes in the answers. Findings from field investigation were then confronted with previous existing concepts of human exposure to natural hazards. Furthermore, the landslide hazard data were analyzed using spatial analysis tools, including GIS scoring, weighting, and overlaying weighted sum. The results showed the level of landslide risk has different values depending on the risk parameter, community vulnerability, and regional capacity. The level of landslide risk was divided into three levels, namely high with an area of 557.71 ha, moderate with 774.49 ha, and low with 1118.77 ha. Each of the risk factors, vulnerability, and capacity, has its characteristics in influencing the landslide risk in Pandansari Village. In relation to landslide disaster management, the risk analysis gives comprehensive input reaching good management practice in Pandansari village.